Islamic Macroeconomics : a Model for Efficient Government, Stability and Full Employment - Almarzoqi, Raja M.; Mansour, Walid; Krichene, Noureddine (London : Taylor and Francis, 2017)
"The economic model in many developed and developing countries is characterized by a 'Big Government' whose intervention limits free competition in the capital, commodity, and labor markets. Since 2009, to remedy mass-unemployment, many leading countries have been locked into an expansionary fiscal policy, repressive money policy, record public and private debts, explosive asset prices, unstable exchange rates, and heightened uncertainties. Likewise, many developing countries have been unable to reach autonomous development despite their vast territories and natural resources, remaining dependent on foreign aid without which they will fall into economic disorder. Islamic Macroeconomics proposes an Islamic model that offers significant prospects for economic growth and durable macroeconomic stability, and which is immune to the defects of the economic models prevailing both in developed and developing countries. An Islamic model advocates a limited government confined to its natural duties of defence, justice, education, health, infrastructure, regulation, and welfare of the vulnerable population. It prohibits interest-based debt and money, and requires full liberalization of all markets including labor, financial, commodity, trade, and foreign exchange markets. The government should be Sharia-compliant in its taxation power and regulatory intervention; it ought to reduce unproductive spending in favor of productive spending. This book is essential reading for students and academics of Islamic economics and finance, economists, practitioners, and researchers."--Provided by publisher.
Chapter 1 Nature and dangers of statism / Raja M. Almarzoqi -- chapter 2 The government from a Sharia perspective / Raja M. Almarzoqi -- chapter 3 Sharia free market model / Raja M. Almarzoqi -- chapter 4 Zakat -- A mandatory redistributive principle of a Sharia model / Raja M. Almarzoqi -- chapter 5 Fiscal policy from a Sharia perspective / Raja M. Almarzoqi -- chapter 6 Nature of money in Sharia / Raja M. Almarzoqi -- chapter 7 On the nature of inflationary financing / Raja M. Almarzoqi -- chapter 8 On the nature of financial repression / Raja M. Almarzoqi -- chapter 9 Sharia banking and capital markets sector / Raja M. Almarzoqi -- chapter 10 A fully liberalized labor market / Raja M. Almarzoqi -- chapter 11 Sharia free trade and foreign exchange policy / Raja M. Almarzoqi -- chapter 12 Growth policy and private sector development / Raja M. Almarzoqi -- chapter Conclusions / Raja M. Almarzoqi.
OCLC-licensed vendor bibliographic record.
Keywords: BUSINESS & ECONOMICS -- Accounting -- Governmental; BUSINESS & ECONOMICS -- Banks & Banking; Economics -- Religious aspects -- Islam; Banks and banking -- Religious aspects -- Islam; Macroeconomics